GLOBAL TAX COMPETITION AND ITS REFLECTIONS ON FOREIGN DIRECT INVESTMENTS: TURKEY-EU ANALYSIS - Yusuf Ekrem AKBAŞ (International Journal of Eurasia Social Sciences, 2017)
The reflections of tax competition in Turkey and six Eurepean Union countries covering the years of 2000-2013 is analysed in this paper. In this context, whether the relationship between corporation income tax and foreign direct investment is analysed with panel data methods. As a result of analysis, the negative relationship between the corporation income tax and foreign direct investment is determined.